Fermentative Production of l-2-Hydroxyglutarate by Engineered Corynebacterium glutamicum via Pathway Extension of l-Lysine Biosynthesis - Prell, Carina; Burgardt, Arthur; Meyer, Florian; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2021)
l-2-hydroxyglutarate (l-2HG) is a trifunctional building block and highly attractive for the chemical and pharmaceutical industries. The natural l-lysine biosynthesis pathway of the amino acid producer Corynebacterium glutamicum was extended for the fermentative production of l-2HG. Since l-2HG is not native to the metabolism of C. glutamicum metabolic engineering of a genome-streamlined l-lysine overproducing strain was required to enable the conversion of l-lysine to l-2HG in a six-step synthetic pathway. To this end, l-lysine decarboxylase was cascaded with two transamination reactions, two NAD(P)-dependent oxidation reactions and the terminal 2-oxoglutarate-dependent glutarate hydroxylase. Of three sources for glutarate hydroxylase the metalloenzyme CsiD from Pseudomonas putida supported l-2HG production to the highest titers. Genetic experiments suggested a role of succinate exporter SucE for export of l-2HG and improving expression of its gene by chromosomal exchange of its native promoter improved l-2HG production. The availability of Fe2+ as cofactor of CsiD was identified as a major bottleneck in the conversion of glutarate to l-2HG. As consequence of strain engineering and media adaptation product titers of 34 ± 0 mM were obtained in a microcultivation system. The glucose-based process was stable in 2 L bioreactor cultivations and a l-2HG titer of 3.5 g L−1 was obtained at the higher of two tested aeration levels. Production of l-2HG from a sidestream of the starch industry as renewable substrate was demonstrated. To the best of our knowledge, this study is the first description of fermentative production of l-2HG, a monomeric precursor used in electrochromic polyamides, to cross-link polyamides or to increase their biodegradability.